2019
DOI: 10.1210/clinem/dgz116
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Acromegaly and the Effect of Treatment: A Systematic Review and Meta-Analysis

Abstract: Background Obstructive sleep apnea (OSA) is a common disorder characterized by upper airway collapse requiring nocturnal ventilatory assistance. Multiple studies have investigated the relationship between acromegaly and OSA, reporting discordant results. Aim To conduct a meta-analysis on the risk for OSA in acromegaly, and in particular to assess the role of disease activity and the effect of treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Improved biochemical control is also associated with a reduction in obstructive sleep apnea (OSA) and apnea-hypopnea index (AHI) assessed by polysomnography. A metaanalysis [30] that included 24 studies (n = 734) showed significant AHI improvement after medical or surgical treatment (effect size − 0.36; 95% CI − 0.49, − 0.23; p < 0.001), and another study of 27 patients [31] showed that 69% of patients with OSA at baseline were cured after achieving acromegaly disease control.…”
Section: What's Newmentioning
confidence: 99%
“…Improved biochemical control is also associated with a reduction in obstructive sleep apnea (OSA) and apnea-hypopnea index (AHI) assessed by polysomnography. A metaanalysis [30] that included 24 studies (n = 734) showed significant AHI improvement after medical or surgical treatment (effect size − 0.36; 95% CI − 0.49, − 0.23; p < 0.001), and another study of 27 patients [31] showed that 69% of patients with OSA at baseline were cured after achieving acromegaly disease control.…”
Section: What's Newmentioning
confidence: 99%
“…The mode of imaging used was also different in the various studies. van Haute et al 3 and Castellani et al 16 used MRI for image acquisition, while Ip et al and Parolin et al 8,18 and Sesmilo et al 17 used computed tomography and teleradiography, respectively. This is the first data on acromegaly and SRBD among Indian subjects although there are several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] OSA is present in up to 90% of patients with active acromegaly and is attributed to changes in soft, cartilaginous, and bony tissues at the level of craniofacial, pharyngeal, and laryngeal structures leading to obstruction of the airflow. [8][9][10][11][12] In addition to the adenoid, uvular, and tonsillar hypertrophy, macroglossia also narrows pharyngeal airway space in acromegaly [8][9][10][11][12] causing air inflow impediment. Data on acromegaly from India are scanty with a single study on a cohort of 271 acromegalic subjects reporting prevalence a of 10.3%, based on clinical questionnaire, with no comment on SRBD.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the presence of obstructive sleep apnea (OSA), which is a common disorder characterized by upper airway collapse requiring nocturnal ventilatory assistance [ 12 ]. Multiple studies have investigated the relationship between acromegaly and OSA, reporting discordant results.…”
Section: Why An Early Diagnosis Is Important: the Clinician’s Poinmentioning
confidence: 99%